What does the literature say about using electronic pillboxes for older adults? A systematic literature review (2019)
Purpose: The purpose of this study is to answer two research questions: (1) What is the clinical evidence for the reported outcomes in studies on electronic pillboxes for older adults? and (2) What is the technology readiness level (TRL) of the electronic pillboxes used, or intended to be used, for older adults? Methods: The scholarly literature was systematically searched and analyzed. Articles were included if they reported results about electronic pillboxes that were used or intended to be used for older adults’ medication. Results: Clinical studies used commercially well-established electronic pillboxes with a high TRL. New electronic pillboxes in development had a low TRL. The discovered outcome was mainly adherence to medication. The overall mean adherence to medication regimens for all the studies using an electronic pillbox was higher than the gold standard of a good adherence level cut-off point (mean adherence 88.8%>80%). However, we found a large variation in this variable (SD = 10.7). With regard to an older adult population’s adherence to medication regimens, for the outcome variable of those who had undergone a kidney transplant, the clinical evidence that electronic pillboxes have a positive impact was strong (1b); for those with a chronic hepatitis C medical condition, the clinical evidence was medium (3), and for those with arterial hypertension and multiple chronic (diabetes and hypertension) medical conditions, the clinical evidence was weak (5). Conclusion: More research is needed in this area using designs that provide greater validity.Implications for Rehabilitation Electronic pillboxes with multiple reminders such as the “voice of a friend” or relative, which implies that electronic pillboxes which adopt “a social role” are advisable. An unequal level of clinical evidence that electronic pillboxes have a positive impact on the adherence outcome variable was found. For new electronic pillboxes still in development that specifically take into account older adults’ needs, the TRL is still low; as a result, they could not be tested in real settings. © 2018, © 2018 Informa UK Limited, trading as Taylor and Francis Group.